Evaluation of basal heave stability of deep excavations in soft clay - Kwek, Zhi Yi (Nanyang Technological University, 2020)
With ever increasing demands for excavations in Singapore due to land scarcity, deep excavation constructions have been frequently carried out in presence of soft clay. One crucial failure often faced during excavation is basal heave stability failure. This mode of failure is highly varying and dependent on numerous parameters which proves essential that reliability and accuracy must be assured when analysing basal heave stability during excavations. As such, this project aims to utilise a finite element analysis method to further investigate and study basal heave stability of deep excavations in soft clay. Traditional methods to evaluate factor of safety for basal heave stability has been developed in the past. For deep excavations, famous examples include Bjerrum & Eide (1956) and Eide et al. (1972) methods. These methods are simplistic, however, possesses several limitations which might provide unrealistic values of factor of safety in certain situations. By utilising Hardening Soil (HS) model with Plaxis2D in this project, it allows for a nonlinear behaviour, inelastic response and stress-dependency soil behaviour to be established. By varying several parameters including wall embedment depth, wall stiffness, excavation width, soil-wall adhesion factor and thickness of clay from bottom of excavation to hard stratum, factor of safety of finite element method will be calculated and plotted to analyse unique trends. These values will then be compared with traditional methods to identify limitations and provide clarification on their reliability and differences. Plastic points plots, along with maximum lateral wall deflections will also be thoroughly analysed to recognise established patterns, along with clear observations and detailed discussions.